Bioremediation and Enzymatic Activities of Pseudomonas fluorescence and Candida parapsilosis - Popoola , B. M. (Innovations in Microbiology and Biotechnology Vol. 8, 2022)
Vegetable oil spills are becoming more common and potentially morechallenging than petroleum hydrocarbon spills. Microbial lipases are well-known biocatalysts that are frequently used in the remediation of vegetable oil spills. For the remediation of locations contaminated with vegetable oil, a thorough characterization of lipase is required. This work was performed to monitor the degradation pattern of vegetable oil. The bioremediation experiment employed two previously isolated microbial isolates from an oil mill in Ibadan, Nigeria. Soil samples from the Nursery section of the Microbiology department, as well as soil samples from the oil mill, were all subjected to various treatment methods. Field bioremediation with the isolates was carried out for 12 weeks, and lipase activity was also determined. Pseudomonas fluorescence and Candida parapsilosis were recognised as the two isolates. The result of sterile soil samples with and without mixing option, from palm oil and palm kernel purposely contaminated soils for all the various treatment,s showed a general increase in total viable counts from the 2nd week to the 12th week, however in thenon-sterilee counterpart there was a steady increase from the 2nd week to the 8th week and subsequently, a gradual decrease from the 10th to the 12th week. Pseudomonas fluorescence and Candida parapsilosis were found to have the potential to degrade fatty waste. As a result, they could be used in the environmental cleanup of the vegetable oil spill site.